2022
DOI: 10.3390/ijms232315386
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Immunologic Properties of the Major Soybean Allergen Gly m 4 Causing Anaphylaxis

Abstract: Gly m 4 is the major soybean allergen, causing birch pollen cross allergic reactions. In some cases, Gly m 4-mediated anaphylaxis takes place, but the causative factors are still unknown. Here, we studied the structural and immunologic properties of Gly m 4 to shed light on this phenomenon. We showed that Gly m 4 retained its structure and IgE-binding capacity after heating. Gly m 4 was cleaved slowly under nonoptimal gastric conditions mimicking duodenal digestion, and IgE from the sera of allergic patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…These results were in c data that were previously obtained for soybean Gly m 4. At 98 °C, the s protein unfolded, but after cooling down to 20 °C, the refolding of Gly m 4 However, as previously described, during heating, Bet v 1 underwent an cess to a random coil structure and partly restored its structure after rec presence of lysolipid LPPG increased the percentage of α-helices in the A and provided greater resistance of the allergen to thermal denaturation, us earlier for soybean Gly m 4 [27] (Figure 3, Table 1).…”
Section: Effects Of Heating On the Structure And Antibody-binding Cap...supporting
confidence: 56%
See 1 more Smart Citation
“…These results were in c data that were previously obtained for soybean Gly m 4. At 98 °C, the s protein unfolded, but after cooling down to 20 °C, the refolding of Gly m 4 However, as previously described, during heating, Bet v 1 underwent an cess to a random coil structure and partly restored its structure after rec presence of lysolipid LPPG increased the percentage of α-helices in the A and provided greater resistance of the allergen to thermal denaturation, us earlier for soybean Gly m 4 [27] (Figure 3, Table 1).…”
Section: Effects Of Heating On the Structure And Antibody-binding Cap...supporting
confidence: 56%
“…These results were in contrast with our data that were previously obtained for soybean Gly m 4. At 98 • C, the soybean allergen protein unfolded, but after cooling down to 20 • C, the refolding of Gly m 4 took place [27]. However, as previously described, during heating, Bet v 1 underwent an unfolding process to a random coil structure and partly restored its structure after recooling [24].…”
Section: Effects Of Heating On the Structure And Antibody-binding Cap...mentioning
confidence: 63%
“…Because soybeans are used in a variety of processed foods, it is conceivable that these multiple allergens may be variably altered by processing methods; however, few studies have conducted a comprehensive variation analysis of such soybean allergens. We generated antibodies against many soybean allergens and analyzed the variation in multiple soybean allergens after gamma irradiation, insect damage, and GM soybeans . Regarding the processing methods, we comprehensively detected soy allergens in miso, a fermented soybean food, and showed that various allergen levels were differentially reduced in different types of miso .…”
Section: Discussionmentioning
confidence: 99%
“…We generated antibodies against many soybean allergens and analyzed the variation in multiple soybean allergens after gamma irradiation, 38 insect damage, 36 and GM soybeans. 39 Regarding the processing methods, we comprehensively detected soy allergens in miso, a fermented soybean food, and showed that various allergen levels were differentially reduced in different types of miso. 20 In this study, we analyzed the variations in various allergens related to natto, another typical fermented food derived from soybeans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation